Efektivitas Model Game Based Learning Berbantuan Media Math Bingo Terhadap Kemampuan Berpikir Kritis Siswa - Siti Mardhiyah; Sofwan Hadi (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
One of the factors for the lack of students' critical thinking skills is learning activities that still use conventional models, where learning is teacher-centered and does not involve students directly and the use of media with technological assistance that has not been maximized. This study aims to (1) determine the difference in students' critical thinking skills between those using the game-based learning model and the conventional model at MIN 3 Ponorogo and (2) determine the effectiveness of the game-based learning model assisted by math bingo media on students' critical thinking skills at MIN 3 Ponorogo. This research uses a quantitative approach with a quasi-experimental type of research. The sampling technique used was purposive sampling. The data collection technique used pretest and postest. The data analysis used was independent sample t-test and N-gain test. The results showed that (1) There is a difference in students' critical thinking skills between those using the game-based learning model and the conventional model. This can be seen from the results of the mean value of each class (2) Game-based learning model assisted by math bingo media is effective to improve students' critical thinking skills. This is based on the results of the N-gain Score test which shows that the average value of the experimental class is 0.76 with a high category or in percent 76.16% with an effective category.